Co-cultures of rat and guinea pig hepatocytes used for the study of species-differences in the proliferation of peroxisomes: I. distinction between hepatocyte subpopulations by catalase cytochemistry - Maier, Monika; Pill, Johannes; Völkl, Alfred; Fahimi, H. Dariush (Acta histochemica et cytochemica, 1992)
In vivo experiments have shown that the magnitude of peroxisomal proliferation induced by xenobiotics varies markedly in different mammalian species. Hepatocytes from rats and guinea pigs In vivo also exhibit species dependent differences in the response to hypolipidaemic drugs. In order to investigate the mechanisms underlying this phenomenon and to rule out the influence of different culture conditions we established a technique for the co-cultivation of primary hepatocytes of rat and guinea pig. Hepatocytes from rats and guinea pigs were isolated by a modified collagenase perfusion technique. Cells were either seeded as homogeneous or mixed populations on standard culture dishes. For their species specific distinction the cells were fixed, stained with the alkaline DAB method for cytochemical demonstration of catalase and embedded in Epon 812. In contrast to rat hepatocytes those of guinea pigs possess not only a peroxisomal but also a cytosolic catalase resulting in a darker cytoplasmic label. Whereas in guinea pig hepatocytes peroxisomes are smaller, forming clusters, they are larger and more sparse in rat hepatocytes. These characteristics are sufficient for the distinction of the hepatocytes of rat and guinea pig in coculture permitting the separate study of their peroxisomes by automatic image analysis. The cocultivation of primary hepatocytes from different mammalian species provides a novel approach for the investigation of interspecies differences in drug metabolism and toxicity studies.
Gesehen am 14.01.2025